Β-Glucosidase from tartary buckwheat immobilization on bifunctionalized nano-magnetic iron oxide and its application in tea soup for aroma and flavonoid aglycone enhancement. Issue 9 (13th August 2019) - Yang, Xilian; Ma, Yanli; Li, Lirong
Abstract : β-Glucosidase (BG) was immobilized on the surface of bifunctionalized nano-magnetic iron oxide with silica and amine groups (Fe3 O4 @SiO2 -NH2 ). Abstract : β-Glucosidase (BG) was immobilized on the surface of bifunctionalized nano-magnetic iron oxide with silica and amine groups (Fe3 O4 @SiO2 -NH2 ). The aroma and flavonoid aglycone enhancement effect of BG in tea soup was investigated. The immobilized BG-synthesized nanocomposite morphology and structure were characterized by using different analytical techniques, including Fourier transform infrared spectroscopy and scanning electron microscopy. The immobilized BG showed enhanced pH and temperature endurance at an optimum pH of 5.0 and temperature of 65 °C. After seven cycles of reuse, immobilized BG showed 51.8% initial activity. Immobilized-BG treatment in green tea and black tea soup elevated the aroma content by approximately 16% and 48%, respectively. In addition, flavonoid aglycones, such as myricetin, kaempferol, and quercetin, in green tea and black tea soup increased by approximately 65- and 5-fold, respectively. These results suggested that immobilized BG showed excellent potential in the enhancement of aroma and effectively hydrolyzed the flavonoid glycosides to release flavonoid aglycones in tea soup. Hence, this study provides a green and sustainable approach for the tea industry to efficiently enhance tea soup properties.